Developments and Recent Progresses in Microwave Impedance Microscope - Zhong, Zhaoqi; Chen, Xiaolong; Quan, Xing; Huan, Huiting; Nian, Fushun; Liang, Shengli; Yang, Yanhong (Frontiers in Physics, 2020)
Microwave impedance microscope (MIM) is a near-field microwave technology which has low emission energy and can detect samples without any damages. It has numerous advantages, which can appreciably suppress the common-mode signal as the sensing probe separates from the excitation electrode, and it is an effective device to represent electrical properties with high spatial resolution. This article reviews the major theories of MIM in detail which involve basic principles and instrument configuration. Besides, this paper summarizes the improvement of MIM properties, and its cutting-edge applications in quantitative measurements of nanoscale permittivity and conductivity, capacitance variation, and electronic inhomogeneity. The relevant implementations in recent literature and prospects of MIM based on the current requirements are discussed. Limitations and advantages of MIM are also highlighted and surveyed to raise awareness for more research into the existing near-field microwave microscopy. This review on the ongoing progress and future perspectives of MIM technology aims to provide a reference for the electronic and microwave measurement community.